2010
DOI: 10.1182/blood-2010-01-264051
|View full text |Cite
|
Sign up to set email alerts
|

Complement anaphylatoxin C5a contributes to hemodialysis-associated thrombosis

Abstract: Thrombosis is a common complication of end-stage renal disease, particularly in patients on hemodialysis. Although substantial progress has been made in preventing thrombotic complications in various other groups of patients, the mechanisms of thrombosis during hemodialysis require clarification. In this report, we demonstrate that complement activation triggered by hemodialysis biomaterials, and the subsequent generation of the complement anaphylatoxin C5a, results in the expression of functionally active tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 43 publications
3
95
0
Order By: Relevance
“…The generation of C5a during haemodialysis-induced complement activation is associated with neutrophil activation and an increase in TF expression as a primary initiator of coagulation. Indeed, patients on haemodialysis have an elevated risk of thrombosis and exhibit increased expression of oxidative stress markers and proinflammatory cytokines — factors that are all strongly correlated with mortality in this population 147,148 . The impact of haemodialysis-induced complement activation on overall inflammation, or even mortality, is difficult to assess given the complexity of the underlying diseases and treatments.…”
Section: Complement-mediated Kidney Diseasementioning
confidence: 99%
“…The generation of C5a during haemodialysis-induced complement activation is associated with neutrophil activation and an increase in TF expression as a primary initiator of coagulation. Indeed, patients on haemodialysis have an elevated risk of thrombosis and exhibit increased expression of oxidative stress markers and proinflammatory cytokines — factors that are all strongly correlated with mortality in this population 147,148 . The impact of haemodialysis-induced complement activation on overall inflammation, or even mortality, is difficult to assess given the complexity of the underlying diseases and treatments.…”
Section: Complement-mediated Kidney Diseasementioning
confidence: 99%
“…Currently, the peptide compstatin and its analogs are the only inhibitors that act on native C3; by preventing activation of C3 by convertases, compstatin blocks C3b opsonization, amplification and generation of effectors. Despite specificity for human/primate C3, compstatin analogs have been tested in models ranging from sepsis to hemodialysis-induced thromboinflammation (11, 22, 23). In a primate model of AMD, intravitreal compstatin suppressed or reversed drusen formation (24), and a compstatin analog (AL-78898A, Alcon) is in clinical development for the treatment of AMD.…”
Section: The Therapeutic Arsenal To Tackle Complement-related Diseasesmentioning
confidence: 99%
“…Patients suffering from end-stage renal disease (ESRD) are often forced to rely for many years on periodic sessions of hemodialysis (HD) because of their deterioration of kidney function and the shortage of donor replacement organs (Santoro et al , 2013). Interestingly, studies have shown that even modern “biocompatible” HD filters can trigger appreciable levels of complement activation and also induce TF expression, thereby contributing to a thromboinflammatory milieu that can increase morbidity in ESRD patients (Kourtzelis et al , 2010). Notably, this thromboinflammatory reaction has been shown to be attenuated ex vivo by the earlier compstatin analog 4(1MeW) (Kourtzelis et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, studies have shown that even modern “biocompatible” HD filters can trigger appreciable levels of complement activation and also induce TF expression, thereby contributing to a thromboinflammatory milieu that can increase morbidity in ESRD patients (Kourtzelis et al , 2010). Notably, this thromboinflammatory reaction has been shown to be attenuated ex vivo by the earlier compstatin analog 4(1MeW) (Kourtzelis et al , 2010). Recently, these findings were recapitulated in a refined, clinically relevant NHP model of HD-induced inflammation (Reis et al , 2014).…”
Section: Introductionmentioning
confidence: 99%